Nutrient intake and unhealthy dietary pattern of Iranian women: a cross sectional study - Hashemi, seyedeh zeinab; Vahidinia, Aliasghar; Hazavehei, Seyed Mohammad Mehdi; Karimi-Shahanjarini, Akram; Poorolajal, Jalal; Erfani, Hossein; Entezari, Mohammad Hassan; Eskandari, Zahra; Shahabadi, Sara Shahabadi (Progress in Nutrition, 2018)
Objective: The present study aimed to assess dietary pattern and nutrient intake of women to determine whether the nutrient intakes meet the Dietary Reference Intakes (DRIs). Methods: This cross-sectional dietary assessment survey was conducted between May and June 2014 in Hamadan city, the west of Iran. A random representative sample of 823 women aged 23-49 years participated in this study. The data collection tool was validated Iranian 168-item semi-quantitative food-frequency questionnaire (FFQ). Participants were classified based on energy intake, into low, normal and high energy groups (